1981
DOI: 10.1128/iai.31.1.252-260.1981
|View full text |Cite
|
Sign up to set email alerts
|

Respective contributions to protection of primary and booster immunization with Escherichia coli heat-labile enterotoxin in rats

Abstract: The respective contributions to protection of the route and dosage of primary and booster immunizations with Escherichia coli heat-labile enterotoxin were evaluated in rats. The degree of protection was determined by challenge with toxin and viable bacteria in ligated ileal loops, and the serum antitoxin response was assayed by enzyme-linked immunosorbent assay. Primary immunization was effective only when given by the parenteral route. The degree of protection was enhanced by a fivefold dosage increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In several studies by Klipstein et al with labile E. coli enterotoxin, it was necessary to prime the mucosal immune system with subcutaneous or intraperitoneal antigen in either complete Freund adjuvant or alum before giving oral antigen (14)(15)(16). Similarly, workers have found parenteral priming to be the key for effective stimulation of the mucosal immune response after subsequent oral antigen administration (5,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies by Klipstein et al with labile E. coli enterotoxin, it was necessary to prime the mucosal immune system with subcutaneous or intraperitoneal antigen in either complete Freund adjuvant or alum before giving oral antigen (14)(15)(16). Similarly, workers have found parenteral priming to be the key for effective stimulation of the mucosal immune response after subsequent oral antigen administration (5,18).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one recent report demonstrates that humans who recovered from gastrointestinal infections due to Vibrio cholera are primed to achieve a memory response to a subsequent parenteral dose of V. cholera (21). Experimental animals primed parenterally with antigen in adjuvant have enhanced local IgA production to subsequent oral administration of the same antigen (5,(14)(15)(16)18).…”
mentioning
confidence: 99%
“…Challenge procedures. Rats were challenged 1 week after the final boost by the instillation of test material into a single 10-cm ligated loop of distal ileum for 18 h as described previously (15,16). Previous studies have established a correlation between significant protection in this assay system and that achieved in rats challenged by intestinal contamination of the intact intestine (19).…”
Section: Methodsmentioning
confidence: 99%
“…boosts is directly related to the total p.o. dosage (15,16). Preliminary observations indicated that the amount of LT needed to achieve significant protection, using two p.o.…”
mentioning
confidence: 99%
“…Development of reliable methods for producing artificially induced immunoprotection against the enterotoxigenic enteropathogens Vibrio cholerae and enterotoxigenic Escherichia coil (ETEC) has been the subject of much investigation [1][2][3][4][5][6]. Numerous experiments with cholera vibrios, cholera toxin, various cholera toxoids and ETEC heat-labile enterotoxin (LT) as immunogens in various animal species have been reported [2][3][4][5]7,8]. These studies generally lead to the conclusion that immunoprotection against V. cholerae and ETEC diarrhea is primarily dependent upon stimulation of an adequate local immune response in the intestine, the primary mechanism being secretion of specific secretory IgA antibody [2][3][4][5][6]9].…”
Section: Introductionmentioning
confidence: 99%